REPRESENTASI PEREMPUAN DALAM FILM SELESAI TAHUN 2021 - Mutiara Nabilah; Mustafa Mustafa (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
Selesai is a film directed by Tompi that has been released in August 2021, this film has successfully entered the trending topic of several social media, such as Twitter, TikTok, and Instagram. This film became a warm conversation by some netizens, there are various compliments about this film, starting from the acting of the cast, the background, and also the cinematography. However, not a few netizens also criticized the film, Tompi was considered to have failed to produce a work because the representation of women was always bad in this film until there was a debate between Tompi and netizens. The purpose of this study is to find out how women are represented in this film, whether in accordance with the opinions said by netizens or vice versa. This research uses descriptive qualitative methods with technical analysis of Sarra Mills critical discourse. The subject of the study was a finished film, with the object of the study being 8 scenes that represent women from various points of view, From the results of the study found that there are 8 scenes that represent women with negative connotations, including women in beautiful clothes represented as cheating, tattooed women are considered naughty and have a dark past, women should not be dominant and should submit to men, and women who have psychiatric problems should be left out, and it is only natural that women are represented as objects of male sexual fantasies.